Strengthening Innovation And Entrepreneurship In Improving SMES Competitiveness - Suharyati, Suharyati (Kesatuan Press, 2020)
MSMEs are able to penetrate Indonesia's GDP by 60%, but the contribution to Indonesia's exports is still lagging behind compared to Southeast Asian countries such as Thailand and the Philippines which have high competitiveness. The economic potential of the Parung district in 2017, seen from the perspective of the MSMEs is at a growth stage. This research analyzes and proves that Innovation and Entrepreneurship influences the competitiveness of MSMEs in Parung district. The population in this study were the MSMEs of Parung subdistrict registered in the MSMEs forum, the sample used was 60 respondents with the Purposive Sampling method. The method used to analyze and interpret data is descriptive statistical analysis using a variance-based Structural Equation Model or called Partial Least Square. The results obtained by all indicators on all variables of this study have met the convergent validity test. The Average Variance Extracted (AVE) value indicates that the entire construct declared valid. The cronbach’s alpha value of all constructs indicating that the construct is declared reliable. The direction of the relationship between Innovation and Entrepreneurship is positive, and Innovation has a significant effect on competitiveness. The direction of the relationship between Entrepreneurship and Competitiveness is positive and Entrepreneurship has a significant effect on Competitiveness. Overall it can be concluded that both Innovation and Entrepreneurship contribute directly to Competitiveness. Thus the increase in Innovation and Entrepreneurship directly affects the improvement of MSMEs Competitiveness. Key words: Competitiveness, Innovation, Entrepreneurship, MSMEs